2004
DOI: 10.1016/s0002-9440(10)63352-4
|View full text |Cite
|
Sign up to set email alerts
|

Near Completely Humanized Liver in Mice Shows Human-Type Metabolic Responses to Drugs

Abstract: Human hepatocytes were transplanted into urokinase-type plasminogen activator-transgenic SCID mice (uPA/SCID mice), which are immunodeficient and undergo liver failure. The transplanted cells were characterized in terms of their in vivo growth potential and functions. The human hepatocytes progressively repopulated the murine host liver. However, the recipients died when the replacement index (RI) of the human hepatocytes exceeded 50%. The hosts (chimeric mice) survived at RI >50% when treated with a drug that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

15
599
0
2

Year Published

2007
2007
2011
2011

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 514 publications
(616 citation statements)
references
References 23 publications
15
599
0
2
Order By: Relevance
“…Many recent publications have unambiguously demonstrated the value of humanized mouse livers for the study of drug metabolism and hepatitis research [7][8][9]21,[23][24][25][26][27][28][29] . However, the albumin-uPA transgenic mouse used for these studies has several major practical limitations.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Many recent publications have unambiguously demonstrated the value of humanized mouse livers for the study of drug metabolism and hepatitis research [7][8][9]21,[23][24][25][26][27][28][29] . However, the albumin-uPA transgenic mouse used for these studies has several major practical limitations.…”
Section: Discussionmentioning
confidence: 99%
“…It was suggested that human complement produced by the donor hepatocytes injured recipient kidneys 7 . We therefore observed several (n = 3) highly repopulated mice for 4 months off NTBC.…”
Section: Repopulation Of Frg Mouse Liver With Human Hepatocytesmentioning
confidence: 99%
See 2 more Smart Citations
“…Finally, the efficacy of human hepatocyte engraftment is highly variable in these animals, ranging from around 2% 73 to 92% after additional treatment with an antibody to asialo-GM-1. 74 Nevertheless, the chimeric uPA mouse model has proven to be useful in studies to determine the efficacy of antiviral compounds. A genotype-dependent antiviral IFN effect in chimeric mice has been observed by several groups.…”
Section: Small-animal Models For Hcv Infectionmentioning
confidence: 99%